The impact of COVID-19 in diabetic kidney disease and chronic kidney disease: A population-based study - Leon-Abarca, Juan Alonso; Memon, Roha Saeed; Rehan, Bahar; Iftikhar, Maimoona; Chatterjee, Antara (Acta Biomedica Atenei Parmensis, 2020)
Background: The spectrum of pre-existing renal disease is known as a risk factor for severe COVID-19 outcomes. However, little is known about the impact of COVID-19 on patients with diabetic nephropathy in comparison to patients with chronic kidney disease. Methods: We used the Mexican Open Registry of COVID-19 patients 11 to analyze anonymized records of those who had symptoms related to COVID-19 to analyze the rates of SARS-CoV-2 infection, development of COVID-19 pneumonia, admission, intubation, Intensive Care Unit admission and mortality. Robust Poisson regression was used to relate sex and age to each of the six outcomes and find adjusted prevalences and adjusted prevalence ratios. Also, binomial regression models were performed for those outcomes that had significant results to generate probability plots to perform a fine analysis of the results obtained along age as a continuous variable. Results:  The adjusted prevalence analysis revealed that that there was a a 87.9% excess probability of developing COVID-19 pneumonia in patients with diabetic nephropathy, a 5% excess probability of being admitted, a 101.7% excess probability of intubation and a 20.8% excess probability of a fatal outcome due to COVID-19 pneumonia in comparison to CKD patients (p